Pengaruh Media Sosial terhadap Konstruksi Identitas Mahasiswa Universitas Jember - Wulansari, Yunita Dwi; Afcarina, Julia Shandra; Zahrafani, Shalsa Aina Widi; Afifah, Wafiatul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Social media is a platform used to communicate virtually for users. Individuals can build their self-image through social media so that it can be seen by other individuals in terms that can be consumed publicly. Social media is considered a second reality as a channel for the main reality. This research aims to find out how much influence social media has in growing a person's identity construction, personal branding, and expanding relationships. This research uses qualitative research methods and uses phenomenological research. Social media can have both negative and positive impacts, according to how it is used. Therefore, you must be wiser in managing social media so that there is no negative impact on yourself or the surrounding environment.